2020
DOI: 10.1016/j.ebiom.2020.102963
|View full text |Cite
|
Sign up to set email alerts
|

Optimal co-clinical radiomics: Sensitivity of radiomic features to tumour volume, image noise and resolution in co-clinical T1-weighted and T2-weighted magnetic resonance imaging

Abstract: Background Radiomics analyses has been proposed to interrogate the biology of tumour as well as to predict/assess response to therapy in vivo . The objective of this work was to assess the sensitivity of radiomics features to noise, resolution, and tumour volume in the context of a co-clinical trial. Methods Triple negative breast cancer (TNBC) patients were recruited into an ongoing co-clinical imaging trial. Sub-typed matched TNBC patient-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 48 publications
3
48
1
Order By: Relevance
“…To our knowledge, this study represents the first such effort to optimize radiomic features in preclinical PET imaging to predict/assess response to therapy in TNBC PDX. We recently characterized the dependency of preclinical MR radiomic features on tumor volume [36]. In this work, we confirmed dependency of preclinical PET radiomic features on tumor volume with strikingly similar clinical parallels.…”
Section: Discussionsupporting
confidence: 76%
“…To our knowledge, this study represents the first such effort to optimize radiomic features in preclinical PET imaging to predict/assess response to therapy in TNBC PDX. We recently characterized the dependency of preclinical MR radiomic features on tumor volume [36]. In this work, we confirmed dependency of preclinical PET radiomic features on tumor volume with strikingly similar clinical parallels.…”
Section: Discussionsupporting
confidence: 76%
“…None of the second- or higher-order features extracted from MR images of our homogenous phantom achieved excellent agreement in the OCCCs. These parameters identified as volume confounded in our study were also reported unstable in the in vivo MRI study by Roy et al, who investigated stability across different tumor volumes on breast cancer patients with T1w and T2w MR sequences [ 29 ]. Therefore, these features do not seem reliable for use in MRI-based texture analysis from differently sized ROIs, and studies based on MR-derived second- and higher-order features should be scrutinized.…”
Section: Discussionsupporting
confidence: 61%
“…In many studies, lesions were marked with ROIs, but the lesions and consecutively the ROIs had different sizes. Considering our results, however, it has to be validated if the ROI size is a pivotal influencing factor in radiomics, for example, by sorting lesions by volume and voxel size and comparing heterogeneities of the radiomic features or by normalizing the features by voxel count or volume [ 17 , 29 , 42 ]. Thus, before applying radiomics in clinical routine, volume as a confounding factor needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to identify whether pSPN is invasive before operation (39). Radiomic analysis has been proposed as a step towards realization of precision medicine by providing means to interrogate the spatial complexity of tumors in vivo (40). Therefore, we try to identify the invasiveness of pSPN by radiomics features and comprehensively consider the effectiveness of different contrastenhanced phases and 2D or 3D segmentation.…”
Section: Discussionmentioning
confidence: 99%